Polish "creative school" by Henryk Rowid: implications for professional development - Marian Piekarski (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The aim of the article is to introduce the profile and achievements of Henryk Rowid, who belongs to the leading Polish educators of the turn of the late 19th and early 20th century. In the background of "work schools" in different countries, the main ideas of the "Polish work school", also called the "creative school", are shown. Rowid, in his programs, refers to the educational role of working, which not only forms the mind but also the attitude of the younger generation. Therefore, we turn to his universal, timeless experiences and try to use them as stimulants in the career development of today's youth.